ANALISIS PENGARUH KONFLIK PEKERJAAN-KELUARGA DAN STRES KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN AFEKTIF SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan Perempuan PT Sai Apparel Industries) - Nur Rahman, Ali Ilmi; Lataruva, Eisha (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to analyze and determine the effect of work-family conflict and Job Stress on employee performance through affective commitment as an intervening variable at PT. Sai Apparel Industries. This study uses work-family conflict and job stress as independent variables, employee performance as the dependent variable, and affective commitment as the intervening variable. The data used in this study are primary data in the form of distributing questionnaires to 90 employee respondents in all departments at PT Sai Apparel Industries. Data was collected through distributing questionnaires to samples selected through non-probability sampling techniques with the Convenience Sampling method. The measurement in the questionnaire uses a Likert Scale. The five hypotheses in this study were tested using quantitative methods and data analysis techniques using path analysis and to test the effect of intervening variables using specific indirect effect tests. The statistical method used is Partial Least Square (PLS). This research data processing uses SmartPLS software version 3.2.9. From the results show that the Work Family Conflict variable has a negative and significant effect on employee performance and a significant negative effect on affective commitment. Job stress has a negative and significant effect on employee performance, and has a significant negative effect on affective commitment. In addition, from the results of intervening tests on specific indirect effects affective commitment variables can mediate the relationship between work-family conflict and job stress on employee performance.